Parents’ experience confronting child burning situation - Oliveira, Valdira Vieira de; Fonseca, Ariadne da Silva; Leite, Maísa Tavares de Souza; Santos, Luciana Soares dos; Fonseca, Adélia Dayane Guimarães; Ohara, Conceição Vieira da Silva (Rev Rene, 2015)
Objective: to understand experiences of parents in a child burning situation during the hospitalization process. Methods: phenomenological research in view of Martin Heidegger, held with seven assisting parents at a pediatrics unit of a general hospital in Montes Claros. The information was obtained by phenomenological interview, containing the question guide: “What does it mean to you being with a son who is suffering with burns?”. Results: during the experience, parents revealed anguish, fear, helplessness, concerns and expectations of “being-in-the-world”. Conclusion: respect, understanding and care from the health team were fundamental for the adaptation and the confrontation demanded by the consequent suffering of the event.